Antiviral activity of mink interferon alpha expressed in the yeast Pichia pastoris - Zhang, Hailing; Zhang, Dongliang; Lu, Han; Zou, Deying; Hu, Bo; Lian, Shizhen; Lu, Shiying (Frontiers in Veterinary Science, 2022)
Farmed mink is an important source of income in northeast China. Although the number of mink farms has decreased significantly due to the diminishing fur industry, approximately eight million mink are bred each year. Many viruses cause infections in mink, including canine distemper, enteritis, and Aleutian disease. These infections are often fatal, resulting in severe economic losses, and current treatments are ineffective. However, research on antiviral interferons has increased in recent years, and antiviral drugs can effectively prevent and control these infections. In this study, the gene encoding a functional mink interferon alpha (MiIFN-α) was cloned into the Pichia pastoris expression vector pPICZαA containing the AOX1 promoter and the α factor secretion signal, and the antiviral activity of the expressed protein was determined. The recombinant plasmid pPICZαA-MiIFN-α was linearized and transformed into the P. pastoris X33 strain, and zeocin-resistant transformants were selected. Protein expression was induced by methanol. SDS-PAGE and western blot analyses showed that a 25 kDa fusion protein was expressed in the culture supernatant, and the purified protein significantly inhibited the cytopathic effect of vesicular stomatitis virus in F81 feline kidney cells, with an antiviral activity of 6.4 × 107 IU/mL. Pharmacokinetic analysis showed that MiIFN-α concentration in rat serum peaked at approximately 36 h after injection. These results lay the foundation for the large-scale production of recombinant MiIFNs.